An exploratory study on the sensory acceptability and quality characteristics of probiotic yogurt with green papaya (Carica papaya L.): promoting underutilized fruit crops - de Gannes, Vidya; Karuppusamy, Sivakumar; Sealey, Ashley; Isaac, Wendy-Ann P. (Frontiers in Sustainable Food Systems, 2025)
Yogurt enriched with underutilized fruits and probiotics offer a promising solution for sustainable food systems. In this study, milk produced locally was fermented with a consortium of active cultures of lactic acid bacteria (LAB) probiotics (Lactobacillus bulgaricus, Lactobacillus acidophilus, and Streptococcus thermophilus) and infused with four levels of local green papaya nectar- 0% (YP0), 5% (YP5), 10% (YP10) and 15% (YP15) to produce four yogurts. The study employed a 4 × 3 complete randomized design giving 12 treatments. The main objectives were: to formulate yogurt incorporating lactic acid bacteria (LAB) probiotics and varying concentrations of green papaya nectar and to evaluate the sensory acceptability and physicochemical characteristics of probiotic yogurt produced with different inclusion levels of green papaya nectar. The LAB count ranged from 6.34–6.36 log10 CFU while pH increased significantly (p < 0.05) during storage. The °Brix value increased significantly (p < 0.05) with higher papaya nectar inclusion levels, which is reflective of the higher total soluble solid content of the green papaya that was incorporated at various concentrations. The color L* value of the yogurts became significantly higher (p < 0.05) during storage indicating they became lighter in color. Sensory acceptability scores revealed that yogurts with higher papaya nectar inclusion were significantly (p < 0.05) more preferred than the control in overall acceptability. At day 7, consistency was significant (p < 0.05) for Y10 and Y15, where consistency improved from 4.33 cm/s to 7.67 cm/s in Y3 and from 5.00 cm/s to 9.83 cm/s in Y4. The results suggest that papaya nectar can be a promising natural additive to improve the sensory appeal of yogurt for sustainable food systems.